Using the finite element method for developing a new model predicting the burst pressure of straight defects in corroded pipes repaired with bonded composite wraps - Metehri, Aicha; Mechab, Belaïd; Bel Abbes, Bachir Bouiadjra (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: This work aims to create a novel model that predicts the burst pressure of straight flaws under internal pressure in corroded pipes that have been repaired with bonded composite wrap. Methods: Geometrical aspects affected the repair performances. The composite patch behaviour strongly depends on several parameters, such as pipe size, defect size, composite ply number, ply orientation, composite properties, and adhesive thickness. The effects of all these parameters on the repair efficiency were analyzed. Results: The obtained results showed that the composite wrap reduces the stress concentration caused by the corrosion defect, which improves the pipe’s long-term durability. Conclusion: The comparison between the new analytically developed model and the finite element (FE) calculations showed good agreement for the repaired corroded pipe.